TC, TN, IC, TOC, CN, and accumulation rates of sediment core PS115/2_2 - Ruediger Stein; Thomas Frederichs; Kirsten Fahl; Walter Geibert; Jens Matthiessen; Frank Niessen; Christoph Vogt; Cynthia Sassenroth; Evgenia A Bazhenova (PANGAEA, 2025)
Sediment Core PS115/2-2 was recovered from the Amundsen Basin in 3600 m water depth at the eastern flank of the Gakkel Ridge during Polarstern Expedition PS115/2 in 2018 (Stein, 2019). The well-dated core is used to reconstruct in detail the interrelationship between ice-sheet dynamics and organic carbon burial in the central Eurasian Basin during the last 430 kyr, and to correlate marine and terrestrial records of the Eurasian Ice Sheet (EIS) history. Using organic-geochemical bulk parameters (i.e., TOC, C/N ratios, Rock Eval) and biomarkers, we have identified prominent well-defined sections with strongly elevated concentration of ancient (petrogenic) predominantly terrestrial OC, coinciding with glacial time intervals of extended ice sheets and the subsequent terminations/deglacials. For the measurement of bulk parameters by means of elemental analysis and Rock-Eval pyrolysis, freeze-dried and homogenized sediments were used. Total organic carbon (TOC) contents were measured by Carbon-Sulfur Analyser (CS-125, Leco) after removing carbonate with hydrochloric acid. Total carbon (TC) and total nitrogen (TN) contents were determined by Carbon-Nitrogen-Sulfur Analyser (Elementar III, Vario). Inorganic (carbonate) carbon (IC) was calculated as IC = TC-TOC. The C/N ratios used as a first-order proxy for estimating the marine (C/N = 5 to 8) and terrestrial (C/N >>10) proportions of the OC, were calculated as "TOC/TN" ratio. As the TN values in sediments from the Laptev Sea continental margin and adjacent deep sea as well as the sediments from Core PS115/2-2 may also contain significant amount of inorganic nitrogen, the C/N ratios of Core PS115/2-2 are certainly minimum values, i.e., when corrected for inorganic nitrogen the maxima of 14 to 16 would increase to 25 and more (cf., Stein & Fahl, 2004). Based on dry bulk density values and linear sedimentation rates, bulk sediment accumulation rates and, by considering TOC values, bulk TOC accumulation rates were calculated (cf., Stein & Fahl, 2004). For further details and methods, we refer to Stein et al. (this paper).
In: Stein, R et al. (2025): A 430 kyr multi-proxy record of Eurasian Ice Sheet history and organic carbon burial in the eastern Eurasian Basin, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.975790